Economic burden of cardiovascular diseases from 2012 to 2017 based on French national claim database. (13th November 2019) - Nicolas, M; Pestel, L; Rivière, S; Rachas, A; Gastaldi-Menager, C
Abstract: Background: The purpose of this study was to assess the economic burden of cardiovascular diseases (CVDs) in France by analysing the structure and the growth of expenditure attributed to these diseases between 2012 and 2017. Methods: For each year, 11 CVDs were identified from SNDS data using algorithms based on long-term disease registry and hospitalization diagnoses, applied to the population of national health insurance general scheme beneficiaries. The individuals' expenditure (26 different items) reimbursed for hospitalisations, ambulatory care and cash payments were included. A top-down method was used to attribute expenditure to each considered groups of diseases based on the average expenditure by disease calculated for individuals with only one disease. To analyse trends, we applied the same methodology from 2012 to 2017. Results: In 2017, of the €140.1 billion reimbursed, €14.0 billion (10.0%) were attributed to the care of 4.0 million people with a CVD (7.0% of the population). Short-stay hospitalisations accounted for 33% of this total expenditure. This proportion was higher for acute CVD (coronary syndrome: 64%, stroke: 56%, heart failure: 65%, pulmonary embolism: 69%) but also for valvular heart disease (50.0%). Medications represented almost 13% of the expenditure attributed to all CVDs, and up to 25% for chronic coronary heart disease. Disability pension essentially concerned sequelae of stroke (12% of the expenditure attributed to this disease). Between 2012 and 2017, the total expenditure attributed to CVDs increased by 3.3% per year, mainly due to the annual mean increase of the number of patients over the period (+3.1%). Conclusions: These results demonstrate the high economic burden of CVDs in France with a detailed analysis of expenditures and their main drivers. The developed tool will help decision makers to monitor the burden of these diseases but also to provide stake holders with a better understanding of trends and regulating actions. Key messages: Economic burden of CVD in France is high: 10% of healthcare expenditure. Implementation of public health policy to prevent CVD and control risk factors must be a priority.